Realizing Inclusive Education in the Era of Industry 4.0: The Role of the PTPN IV Dolok Ilir School Website - Tulus; Marpaung, T.J.; Suriati (Talenta Publisher, 2023)
Inclusive education has become an increasingly important aspect in addressing the dynamics of the industry 4.0 era. To realize inclusive education at PTPN IV Dolok Ilir School, the utilization of digital technology, particularly the school website, is being employed. Inclusive education aims to provide equal and sustainable access to education for all students, including those with special needs. The application of technology in the form of a school website has opened up broader access for students, parents, and educational stakeholders. In the context of PTPN IV Dolok Ilir School, this website serves as an information hub providing a variety of learning materials, schedules, announcements, and interactions among teachers, students, and parents. Furthermore, this website system ensures high transparency in facilitating better communication between the school and students' families. The key role of digital technology in assisting in the creation of an inclusive educational environment at PTPN IV Dolok Ilir School results in increased access to education, student empowerment, and greater parental involvement in supporting their children's educational development. The broader implications of this approach include a positive contribution to the quality of education in an era dominated by technological change and ensuring that no student is left behind in reaching their full potential.